The Impact of Entrepreneurship-Based Branding on Startup Performance - Rahimi, Elahe; Heidari, Abbas; Ghasemi, Behrooz (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2024)
Objective: The purpose of this study is to examine the influence of entrepreneurship-based branding on the performance of startups.Methodology: For this purpose, 52 managers or representatives of startups in the public services sector were considered as the population. Due to the small size of the population, no sampling was conducted, and all 52 individuals were studied. The research data were collected using a researcher-made questionnaire.Findings: The results indicate that entrepreneurship-based branding has a positive and significant impact on the performance of startups. Specifically, causal conditions of branding with a statistic of 26.719 have a significant impact on entrepreneurial branding; entrepreneurial branding with a statistic of 4.873 significantly influences value-based brand positioning; value-based positioning with a statistic of 29.960 significantly affects startup performance.Conclusion: The formulation of practical strategies, such as improving responsiveness, and the efficient and effective employment of this sector, leads to the strategic development of the brand in domestic and foreign markets, which in turn, will lead to an enhanced brand identity. On the other hand, having professional management, marketing experience, resource commitment, and the utilization of internal information contributes to the development of entrepreneurship.